Promotion of Diffused Light Storage - International Potato Center (International Food Policy Research Institute, 2014)
This dataset includes constructed diffused light storage (DLS) number. Project title: Promotion of Diffused Light Storage. Project abstract: Storage losses including impaired quality are partly caused by harvested crops not being stored in a product specific manner. Diffused Light Storage (DLS) is a post-harvest technology which uses natural indirect light instead of low temperature to control excessive sprout growth of potato seeds, extend their storage life, reduce the associated storage losses and improve productivity of the potato crop. It is a low cost method which provides a new opportunity for farmers to preserve the quality of seed potato. Quality Declared Planting Material (QDPM) is a value added product and must be stored in DLS. Project website: http://africa-rising.net